Refining the Behavioral Phenotype of Angelman Syndrome: Examining Differences in Motivation for Social Contact Between Genetic Subgroups - Heald, Mary; Adams, Dawn; Walls, Emily; Oliver, Christopher (Frontiers in Behavioral Neuroscience, 2021)
Angelman syndrome (AS) is caused by loss of information from the 15q11.2-13 region on the maternal chromosome with striking phenotypic difference from Prader-Will syndrome in which information is lost from the same region on the paternal chromosome. Motivation for social contact and sensory seeking behaviours are often noted as characteristics of the phenotype of Angleman syndrome and it has been argued that the strong drive for social contact supports a kinship theory interpretation of genomic imprinting. In this study we developed an experimental paradigm for quantifying the motivation for social contact in AS and examined differences across the genetic subtypes that causes Angelman syndrome (deletion, imprinting centre defect (ICD), uniparental disomy and UBE3A mutation). Using single case experimental designs we examined the rate of acquisition of behavioural responses using operant learning paradigms for 21 children with AS whilst systematically varying the nature of social and sensory reinforcement. Variability in rates of acquisition was influenced by the nature of rewarding stimuli. Across the total sample both sensory stimuli and social contact could increase the rate of rewarded behaviour with difference between children in the most effective reward. A striking difference in the rewarding properties of social contact across genetic subtypes was evidenced by non-deletion genetic causes of AS showing significantly higher rates of responding in the reinforcement paradigm than for the deletion cause. The results indicate that reinforcer assessment can beneficially inform behavioural interventions and that within syndrome variability in the behavioural phenotype of AS is likely driven by genetic difference. The non-deletion cause of AS, and particularly the ICD group, may be the optimal group for further study of genomic imprinting.